2015
DOI: 10.1038/aps.2015.110
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide interacting regulator of TRP (Pirt) enhances TRPM8 channel activity in vitro via increasing channel conductance

Abstract: Aim: Pirt is a two-transmembrane domain protein that regulates the function of a variety of ion channels. Our previous study indicated that Pirt acts as a positive endogenous regulator of the TRPM8 channel. The aim of this study was to investigate the mechanism underlying the regulation of TRPM8 channel by Pirt. Methods: HEK293 cells were transfected with TRPM8+Pirt or TRPM8 alone. Menthol (1 mmol/L) was applied through perfusion to induce TRPM8-mediated voltage-dependent currents, which were recorded using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…3A). This agrees with previous similar studies of the mouse orthologs, which show that mouse TRPM8 membrane trafficking is also not affected by mouse PIRT coexpression and that mouse PIRT increases single channel conductance (12)(13)(14).…”
Section: Pirt Modulation Of Trpm8 Is Species-dependentsupporting
confidence: 93%
See 2 more Smart Citations
“…3A). This agrees with previous similar studies of the mouse orthologs, which show that mouse TRPM8 membrane trafficking is also not affected by mouse PIRT coexpression and that mouse PIRT increases single channel conductance (12)(13)(14).…”
Section: Pirt Modulation Of Trpm8 Is Species-dependentsupporting
confidence: 93%
“…Cell-surface trafficking experiments indicate that enhanced channel activity in mice is not caused by changes in expression levels or channel trafficking, supporting the idea that PIRT enhances channel activity by interacting directly with the channels rather than increasing the number of channels in the membrane (12,14). More recently, it was shown that PIRT works synergistically with PIP 2 to enhance TRPM8 currents by increasing conductance at the single channel level (13). However, the details of this interaction including the binding site and stoichiometry of PIRT to TRPM8 are unknown.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…TRPM8 channel function is reportedly modulated by G-protein coupled receptors [ 34 ], phosphoinosites [ 15 ], serine/threonine [ 35 ] and tyrosine kinases/phosphatases [ 36 ], as well as UBA1-dependent ubiquitination [ 19 ]. Moreover, protein-protein interactions with the two-transmembrane domain protein Pirt [ 37 ] and the TRP channel-associated factors (TCAFs) [ 38 ] reportedly promote trafficking and/or modulate activity of TRPM8. Finally, picomolar concentrations of testosterone have been shown to stimulate openings of the purified TRPM8 channel protein in planar lipid bilayers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We show that PIRT specifically binds oxytocin. It is plausible that PIRT is involved with oxytocin regulation given that the oxytocin receptor is a G qα type G protein-coupled receptor (GPCR), G qα GPCRs directly influence PIP 2 levels, GPCRs are implicated with TRP channels, and PIRT is a PIP 2 binding protein that functionally modulates TRP channels [12][13][14]23,25,[76][77][78]. Similarly, PIRT was shown to be important for uterine contraction pain under oxytocin insult during birth in mice [14].…”
Section: Discussionmentioning
confidence: 99%